Scientific and regulatory challenges in evaluating clinical trial protocols for HIV-1/AIDS vaccines – A review from a regulatory perspective. Issue 2 (March 2016) - Sheets, Rebecca L.; Zhou, TieQun; Knezevic, Ivana
Abstract: Clinical development of prophylactic HIV/AIDS vaccines presents many scientific challenges that result in challenges for regulators reviewing clinical trial applications (CTAs). The World Health Organization (WHO) has the responsibility to provide technical support to these regulators. The search for an HIV/AIDS vaccine will only succeed through well-designed, -conducted and -controlled human efficacy studies reviewed and approved by regulators in countries worldwide, particularly in countries where the epidemic has hit hardest, such as in sub-Saharan Africa and Asia. This review summarizes the current candidates in development and focuses on challenges regulators face when reviewing CTAs, such as the evolving landscape of "standard of prevention, " trials in adolescents, adaptive trial designs, correlates of protection and their analysis, and access to successful vaccines. There are many unknowns in the field of HIV/AIDS vaccine development and often, there is not a clear right or wrong approach because of the scientific challenges described in this review. Consequently, regulators should not feel that decisions need be made in isolation, when there are many available international collaborative efforts and opportunities to seek expert advice. The WHO provides many such opportunities and support to regulators across the globe.